2011
DOI: 10.1016/j.tcb.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the enigma: progress towards understanding the coronin family of actin regulators

Abstract: Coronins are a conserved family of actin cytoskeleton regulators that promote cell motility and modulate other actin-dependent processes. Although these proteins have been known for twenty years, substantial progress has been made in the last five years towards understanding coronins. Here, we review this progress, place it into the context of what was already known and pose several questions that remain to be addressed. In particular, we cover the emerging consensus about the role of Type I coronins in coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 57 publications
1
139
0
Order By: Relevance
“…CORO1A belongs to a family of WD40 domain-containing proteins that control diverse aspects of F-actin polymerization and branching cycle. It binds filamentous actin, Arp2/3 complex (Chan et al, 2011) and regulates the plasma membrane localization and activation of Rac1 (Castro-Castro et al, 2011). On the other hand, GIT1 functions as an integrator of signaling pathways controlling vesicle trafficking, adhesion, and cytoskeletal organization.…”
Section: Discussionmentioning
confidence: 99%
“…CORO1A belongs to a family of WD40 domain-containing proteins that control diverse aspects of F-actin polymerization and branching cycle. It binds filamentous actin, Arp2/3 complex (Chan et al, 2011) and regulates the plasma membrane localization and activation of Rac1 (Castro-Castro et al, 2011). On the other hand, GIT1 functions as an integrator of signaling pathways controlling vesicle trafficking, adhesion, and cytoskeletal organization.…”
Section: Discussionmentioning
confidence: 99%
“…One model suggests that Coronin-1A and -1B together coordinate Arp2/3 assembly and actin depolymerizing factor (ADF)/cofilin disassembly, enhancing the flux of actin through the filament assembly/disassembly cycle [33, 34]. Finally, translocation of Rac1 to the plasma membrane also involves Coronin-1A, which in concert with other proteins, including ArhGEF7, Pak1 and RhoGD1α, sets up a relay mechanism to amplify Rac1 signals in response to F-actin polymerization or other changes induced by engagement of cell surface receptors and co-stimulatory molecules [35].…”
Section: Coronin-1a: Structure Binding Partners and Mechanisms Of Acmentioning
confidence: 99%
“…In addition, recent studies have identified inhibitory proteins for the Arp2/3 complex and have elucidated the mechanisms that cause retraction of lamellipodia and ruffles (Chan et al, 2011;Dang et al, 2013). However, we still ignore the mechanism of initiation of lamellipodia and ruffles because the origin and availability of the pre-existing mother filaments mediating initial activation of the Arp2/3 complex remain unknown.…”
Section: Introductionmentioning
confidence: 99%